The case of successful therapy with Nilotinib in patients with Ph-positive chronic myelogenous leukemia of chronic phase resistant to Interferon and Gleevec - N. A. Afanasyeva; G. A. Gusarova (Онкогематология, 2022)
In spite of striking successes achieved in the treatment of chronic leukemia with Gleevec, some patients remain resistant to the drug. Risk for development of resistance to Gleevec increases with the duration of chronic phase of disease and, more evidently, with onset of acceleration phase and blast crisis. Besides, other patients can not tolerate Gleevec. Nilotinib (tasigna, Novartis Pharma) which is a new highly selective inhibitor of bcr/abl tyrosine-kinase has been introduced into clinical practice after the mechanisms of resistance to drug became clear. Clinical trials of phase I and II demonstrated high activity of Nilotinib in patients with resistance to Gleevec, low toxicity profile and absence of cross toxicity with Gleevec. The clinical case of successful therapy with Nilotinib in patient with cytogenetically proved resistance to Gleevec is reported in the article. The major cytogenetic response was achieved after a short period of time (6 months) with acceptable tolerability of treatment.